Konsep Muhasabah sebagai Kesadaran Reflektif dalam Evaluasi Amal: Kajian terhadap Kitab Syarah Al-Hikam - Muhammad Rizqi Alfaeni; Suci Hardianti; Muhammad Wildan Firdaus; Dianawati; Moch. Mahdiyan Nasikhin (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the concept of muhasabah as reflective consciousness in the evaluation of deeds based on Syarah Al-Hikam by Ibn ‘Athaillah al-Sakandari. The research employs a library research method using content analysis. Data were collected from relevant literature, including books, scientific journals, and previous studies, and analyzed systematically to obtain a comprehensive understanding. The findings indicate that muhasabah represents a form of reflective consciousness that functions not only as self-evaluation but also as a means of spiritual purification (tazkiyatun nafs) in Islam. In the perspective of Al-Hikam, the evaluation of deeds emphasizes sincerity, self-awareness, and spiritual connection with Allah SWT. Reflective consciousness serves as a fundamental element in shaping character and improving the quality of Muslim actions.